METHODS OF PUTTING INTO PRACTICE THE VISUAL PRESENTATION OF THE CONTENT AND ESSENCE OF CHEMISTRY EDUCATION TO STUDENTS - Qalandarov Farhod Astonaqulovich (American Journals, 2023)
Some examples of pedagogical skills and their corresponding audiovisual tools, the types of reception of information provided and the possibilities of independent preparation of this information were considered.
Keywords: Chemistry education, visual, visual presentation, pedagogical techniques, static projection tools, etc.